Analysis of the Understanding Profile of PPG DALJAB Students Regarding the Pancasila Profile Student in Mardeka Curriculum Learning - Hunaepi, Hunaepi; Suastra, I Wayan; Atmadja, Ananta Wikrama Tungga (Empiricism Journal, 2023)
This research aims to analyze the understanding of PPG Teachers regarding the profile of Pancasila Students in the context of the Merdeka Belajar Curriculum. The research employed a descriptive study method, involving 37 PPG students in Category I In-Service Training, batch 3 of the year 2023 at the University of Education Mandalika as respondents. The instrument used was a closed questionnaire with 5 indicators, covering teachers' understanding of Pancasila values, integration of Pancasila values in teaching modules, perceptions of the relevance of Pancasila values in the learning process, the impact of implementing the Pancasila student profile, and challenges faced in integrating Pancasila values. The questionnaire was validated and tested for reliability, yielding a Cronbach's Alpha value of 0.872. The research findings indicate that PPG students have a good understanding of Pancasila values. However, challenges exist in effectively integrating these values into the learning process. Potential recommendations for further research suggest exploring various aspects to provide a more comprehensive insight into the integration of Pancasila values within the Merdeka Belajar Curriculum context. Key areas of focus include effective teaching strategies, the influence of curriculum implementation, training and development for teachers, and student participation. Further research in these areas is expected to contribute significantly to understanding and implementing Pancasila values in education.